2000
DOI: 10.1093/toxsci/53.2.392
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prenatal Aflatoxin B1 Exposure on Behaviors of Rat Offspring

Abstract: The effects of prenatal aflatoxin B1 (AFB) exposure on eight behavioral parameters in Jcl:Wistar rat offspring were assessed. Pregnant rats were injected subcutaneously with 0.3 mg/kg/day of AFB dissolved in dimethylsulfoxide on days 11-14 (Group A) or 15-18 (Group B) of gestation. Controls received the vehicle similarly on days 11-18 of gestation. Before weaning, the offspring were examined using the cliff avoidance response (5 days of age), the negative geotaxis reflex (7 days), and swimming development (6, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…Despite less evidences that confirmed an adverse effect of MWCNTs on neurobehavioral development in the present report, it is important to note that stage of pregnancy is important factor that can influence the risk to the fetus. Because exposure to various substances in early pregnancy (e.g., time exposure to MWCNTs in the present study) can induce lower developmental interference than other stage such as mid-organogenesis (Kihara et al, 1991;Koren and Pastuszak, 1998). Thus exposure to these nanomaterials in the other stage of pregnancy may induce far more destructive effects on fetus development.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Despite less evidences that confirmed an adverse effect of MWCNTs on neurobehavioral development in the present report, it is important to note that stage of pregnancy is important factor that can influence the risk to the fetus. Because exposure to various substances in early pregnancy (e.g., time exposure to MWCNTs in the present study) can induce lower developmental interference than other stage such as mid-organogenesis (Kihara et al, 1991;Koren and Pastuszak, 1998). Thus exposure to these nanomaterials in the other stage of pregnancy may induce far more destructive effects on fetus development.…”
Section: Discussionmentioning
confidence: 79%
“…Mice were tested for 5 min in an open field apparatus consists of a bright square with a diameter measuring 100 cm. The time of movement including walking or running (ambulation) and the time spent in the inner area of the arena (> 5 cm away from any wall) were monitored as locomotor activity and anxiety indices, respectively (Kihara et al, 1991;Wolansky et al, 2008). All parameters used to assess behaviors were recorded by a camera at the right angle above the open field apparatus.…”
Section: Psychobiological Evaluations Of Pups Open Field Test: Oftmentioning
confidence: 99%
“…Abdelhamid (2005) found that aflatoxin lowered the fertility to 13% and increased the mortality of embryos. Kihara et al (2000) indicated that prenatal exposure to AFB 1 produced a delay of early response development, impaired locomotor coordination, and impaired learning ability in the offspring of rats exposed to AFB 1 during mid-pregnancy, and early gestational exposure appeared to produce greater effects than later exposure. Although detection of AFB 1 in blood samples was confirmed by TLC (Abdelhamid et al 1999), HPLC, as well as by mass spectral analysis with standard errors (Tsuboi et al 1984), aflatoxin-serum albumin adducts have a longer half-life than low molecular weight aflatoxin derivatives which may be excreted rapidly.…”
Section: Discussionmentioning
confidence: 99%
“…4 Albino rats weighing 100-150 g were taken. The animals were placed individually on a scraped rod of 7 cm in diameter and rotating at a rate of 5 revolutions per minute.…”
Section: Forced Locomotor Activity (Rota Rod Test)mentioning
confidence: 99%